ANALISIS PENERAPAN MANAJEMEN RISIKO PADA PT. INDOFOOD - Davania Anazra, Davania Anazra; Syabilla Putri Affani; Intan Vilja Aura Fazia; Arsyadona (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
This study analyzes the implementation of risk management at PT Indofood Sukses Makmur Tbk, a leading company in Indonesia’s food and beverage industry, in facing modern business challenges. The study highlights the Enterprise Risk Management (ERM) approach Indofood uses to identify, assess, and manage various risk types, including operational, market, raw material price, climate change, sustainability, and COVID-19 pandemic risks. Results indicate that the comprehensive risk management implementation supports the company’s resilience to market fluctuations, reduces financial impact, and maintains operational stability. This journal underscores the importance of risk mitigation strategies for corporate sustainability in a dynamic business environment. Keywords: Risk management, ERM, PT Indofood, sustainability, COVID-19 pandemic